Miniaturizing Large Hadron Collider (LHC): charged particle dynamics in electromagnetic field - Liu, Shukun (Nanyang Technological University, 2025)
This dissertation investigates the behavior of charged particles in electromagnetic fields, emphasizing both theoretical and computational perspectives. The study addresses the intricate dynamics of charged particle motion, which are critical to advancements in fields such as particle physics, plasma research, and electromagnetic device design. By exploring the interplay of classical and relativistic effects, the research seeks to enhance our understanding of particle trajectories under diverse electromagnetic conditions.